Circuito simulador de movimentação veicular com joystick - Araújo, Victor Volochtchuk de (2020)
This work presents a simplified system for the simulation of an electric vehicle using a joystick. The work was designed with the intention of providing a way for people with motor limitations to use autonomously a vehicle. For this project, communication with CAN bus was used in order to bring the experiment closer to the automotive world, since this type of communication is widely used in vehicles that are available to the population. For the realization of the project, 2 Arduino Leonardo boards were used due to the practicality of general assembly of the necessary circuit, the facility for programming the system, as well as the familiarity that the author has with the material. MCP2515 modules were used together, responsible for managing the CAN bus and sending / receiving messages through the bus and the L298N H-bridge module, responsible for driving the electric motor. As a sensor and actuators we have a joystick, which is responsible for sending the signals for movement and a SG90 servo motor, to simulate the steering system and an electric motor to simulate the motor itself. As a result, the author verified that the system worked as expected, causing the steering and engine activations through a joystick present on the other side of the CAN bus, in relation to the actuators. The author proposed as future actions a greater proximity of companies for possible industrial implementation, first in electric vehicles and after joining this technology and developing in combustion vehicles.